STUDY OF THE INFLUENCE OF THE DIMENSIONS OF THE CYCLONE INLET ON THE CYCLONE PERFORMANCE - Xodjiyev Muxsin Todjiyevich; Murodov Orif Jumayevich; Adilova Aziza Shuxratovna; Saidova Nozima A’lovidinovna (Western European Studies, 2024)
The article presents the results of studies of the influence of the dimensions of the cyclone inlet on the performance of the cyclone and the structure of the flow field. The studies were carried out using calculations using the Reynolds Stress Turbulence Model (RTST). The results show that the maximum tangential velocity in the cyclone decreases with increasing size of the cyclone inlet. Increasing the size of the cyclone inlet led to a decrease in pressure drop. However, the cut-off diameter of the cyclone increased with the size of the cyclone inlet, where the efficiency of the cyclone decreased due to the weak vortex force. According to the results obtained, changing the dimensions of the width of the cyclone inlet had a greater effect on the cut-off diameter than the height of the cyclone inlet.
Keywords: Cyclone; Stairmand; dust